Disparities in time to start of definitive radiation treatment for patients with locally advanced cervical cancer. Issue 5 (15th April 2022) - Kotha, Nikhil V; Williamson, Casey W; Mell, Loren K; Murphy, James D; Martinez, Elena; Binder, Pratibha S; Mayadev, Jyoti S
Abstract : Background: Chemoradiation or radiation therapy alone are curative standards for patients with locally advanced cervical cancer. Objective: To investigate factors that influence time to initiation of chemoradiation or radiation and the subsequent impact of time to treatment on recurrence and survival outcomes. Methods: Patients with locally advanced cervical cancer treated with definitive chemoradiation or radiation at our institution between November 2015 and August 2020 were retrospectively identified. Time to treatment initiation was defined as the number of days from date of diagnosis (via biopsy) to the start date of radiation. The cohort was stratified by the median time to treatment into early (<75 days) and delayed (≥75 days) cohorts. Multivariable logistic regression was conducted to examine factors associated with delayed time to treatment. Results: We identified 143 patients with locally advanced cervical cancer who underwent definitive chemoradiation or radiation. Median follow-up time was 18 months (range 2–62). A total of 71 (49.7%) patients had time to treatment <75 days and 72 (50.3%) patients had time to treatment ≥75 days. The delayed cohort had a higher proportion of Hispanic patients (51.4% vs 31.0%, p=0.04). In multivariable modeling, Hispanic women were 2.71 times more likely (p=0.04) to undergo delayed time to treatment than non-Hispanic white women. Additionally, patients with stage >IIB disease were less likely to undergo delayed time to treatment (OR 0.26, p=0.02) than patients with stage <IIB disease. There was no interaction between race/ethnicity and disease stage. Delayed time to treatment was not associated with inferior overall survival, loco-regional failure, or distant failure. Conclusion: Hispanic patients with locally advanced cervical cancer were more likely to receive delayed time to definitive treatment of ≥75 days. Further studies examining the presence of similar disparities in delay to definitive treatment for locally advanced cervical cancer at other institutions and settings are warranted.